Visualization study of a flat confined loop heat pipe for electronic devices cooling. (15th September 2022) - Wang, Xianling; Yang, Jingxuan; Wen, Qiaowei; Shittu, Samson; Liu, Guangming; Qiu, Zining; Zhao, Xudong; Wang, Zhangyuan
Highlights: A visualization experiment of the FCLHP was conducted. The regular rewetting of the heated surface was allowed by the open flow space. The intermittent boiling can be induced by the evaporator outlet restriction. Compared with the MCFLHP, the thermal resistance of the FCLHP was reduced by 29%. Abstract: Aiming to alleviate the 'dry-out' phenomenon of evaporators with microchannels and cater to the thermal management requirements of electronic devices, a novel flat confined loop heat pipe (FCLHP) was proposed, making its first attempt to provide an open flow space over the microchannel top surface of the evaporator. The internal flow to be confined in only one direction and the bubble to expand freely in the open space was allowed. Meanwhile, the evaporator and condenser were visualized to investigate the operation performance and mechanism of the FCLHP under different heat loads and cooling capacity. The intermittent boiling mechanism of the FCLHP was revealed. The results indicated that the regular rewetting of the heated surface was allowed by the open flow space over the microchannels. The proposed FCLHP could work most effectively as the cooling water temperature was 23 °C and cooling water flow rate was 135 mL/min, under which the FCLHP could start up most quickly; the operating temperature was reduced by 10% at most, and the minimum thermal resistance was just 0.12 K/W. The temperature fluctuation was related to intermittent boiling, and with the increase of heat load, the period of intermittent boiling decreased and then stayed constant. This can be explained as the fact that when the boiling was fully developed, the occurrence of intermittent boiling was attributed to the evaporator outlet restriction. Compared with the conventional MCFLHP in the literature, the proposed FCLHP can successfully start up at a lower heat load, i.e., 30 W; the temperature fluctuation of Teo was greatly reduced to less than 1 °C, and the thermal resistance was reduced by 29%. This research will be useful for the engineers and researchers in the application fields of heat pipes.